The downward spiralling nature of the North Atlantic Subtropical Gyre - Sara Berglund (Nature Communications, 2022)
By tracing northward flowing Atlantic water, here the authors show that before this water leaves the North Atlantic Subtropical Gyre and continues northwards, most of it circulates around the gyre while becoming denser through mixing.